PERBANDINGAN PRESTASI BELAJAR SISWA SISTEM FULL DAY SCHOOL DAN SISTEM REGULER KELAS IV SEKOLAH DASAR TAHUN AJARAN 2019/2020 DI KECAMATAN KEBUMEN - afrida conniestia ikhsani; Suhartono Suhartono; Ratna Hidayah (Universitas Sebelas Maret, 2020)
The education system in Indonesia is divided into two types, namely the education full-day school system and the regular system. These two systems have differences in the length of study time, the emotional level of students, and the fatigue of students. The fatigue will greatly affect students in terms of learning which will also affect the level of student achievement during school. The study aimed to explain the differences between full-day school system and regular system on student learning achievement to fourth grade of elementary school. It used comparative quantitative research methods. Data collection techniques were observation and tests. Data analysis used test Independent Sample T-test. The result of the research indicated that there were differences between full-day school system and regular system on student learning achievement to fourth grade of elementary school in Kebumen sub-districts in academic year of 2019/2020. The Sig value on the independent sample t-test was 0.034. It meant that Sig value was 0.000